Peculiarities of Athletes’ Adaptation and Preparation for 24th World University Games in Bangkok (Baltic Journal of Sport and Health Sciences, 2018)
Travelling across several time zones exposes the sportsman to a shift of his internal biological clock and the result is a transient desynchronization of the circadian rhythm lasting for several days until the body adapts to new environmental conditions. The subjects of this study were 12 Lithuanian Track and Field athletes participating in the 24th University Games in Bangkok. We used the model of integral evaluation of the body functioning during exercise which integrates changes of three functional elements: P — periphery system (muscles), R — regulatory system (brain), S — supplying system (heart, blood-vessel system). A Finger Taping Test, where the time intervals were recorded in milliseconds between separate motions, and a nonlinear dimensional reduction by grouping them to various components were used for analysis. We observed a lot of changes in various indices but the main attention was paid to the assessment of indices providing information about the mobilization and recovery of the cardiovascular system and the complexity of body functioning. After the arrival the characteristic feature was a slower mobilization of the body functions at the onset of exercise for the first 4—5 days, though the level of mobilization during the exercise remained the same. Another characteristic feature was the slower recovery of cardiovascular indices after exercise for the first 6—7 days. There were some phases in the process of adaptation after sudden change of geographical and environmental conditions before competition. The first phase of activation of regulatory systems occurred, and the phase of increased energy demands appeared after 48 hours and lasted for the next five days. A wide range of individual variations characteristic of adaptive changes in the body depended on training and competitive experience of athletes, their personality, sleep and behavior habits and training loads performed before departure to the venue of competitions as well. The behaviour of athletes and training strategies during the first days were important and could help accelerate the adaptation. And on the contrary, heavy training loads could decrease the speed of adaptive changes.Keywords: cardiovascular system, complexity, recovery, adaptation